Hekate : goddess of witches - Weber, Courtney (Weiser Books, 2021)
"This book offers a deeply informed but accessible journey through lore and history of Hekate, the ancient goddess of crossroads, ghosts, and witchcraft. Hekate's relevance today is explored, along with tools and techniques to incorporate this goddess into your personal journey. The spiritual content is accessible to anyone with an interest in witchcraft, regardless of their faith or background. The book also explores magickal ethics, what it means to be a witch in the 21st century, and best practices for successful witchcraft"--